CircDCAF6 promotes myoblast differentiation by inhibiting the ubiquitination of ACTC1 - Liang Chengcheng; Yu Shengchen; Hina Sultana; Zhao Chunping; Cheng Gong; Sameerh Alsahafi; Safa H. Qahl; Fatimah A. Alqahtani; Dalal Alenizi; Dalal Alardan; Linsen Zan (Functional & Integrative Genomics, 2026)

Non-covalent interactions between lignin and cellulase: From molecular mechanisms to precision regulation - Chengcheng Ye; Yuchen Han; Yanyi Tao; Lin Lv; Yu Long; Jianfeng Wu; Yongcan Jin; Wenjuan Wu (Bioresource Technology, 2026)

Synergy between lacustrine groundwater discharge and dissolved organic matter in regulating seasonal CH4 and CO2 emissions in an ice–covered lake–groundwater system - Yuanzhen Zhao; Lijuan Hu; Shen Qu; Heyang Sun; Chengcheng Xia; Chao Gu; Xu Yang; Zhongli Wang; Limin Duan; Xiaomin Liu; Ruihong Yu (Journal of Hydrology, 2026)

Valorization of bigeye tuna (Thunnus obesus) bone by-products via steam explosion: Novel umami peptides with synergistic taste enhancement and sodium reduction potential - Yi-Qi Zhang; Chengcheng Li; Lai Wei; Dongcheng Li; Xinyi Yu; Jiajia Wu; Zhiyuan Dai; Yanbin Lu (Food Chemistry, 2026)

Multi-media antibiotics, intracellular and extracellular antibiotic resistance genes in marine protected areas of the South China Sea: Spatiotemporal distribution and multi-factor drivers of dissemination - Chengcheng Bu; Limin Ma; Yu Hua; Shaopeng Xu; Yutong Zhang; Huadong Yi; Yuchen Han; Haoyu Zeng; Yongzhi Wang; Xiaoying Xu; Qihui Zhao; Ruolan Jia; et al. (Marine Pollution Bulletin, 2026)

Efficient degradation of ceftiofur sodium via a water falling film plasma system: Process modeling and mechanistic insights - Jianquan Li; Donglin Hou; Chengcheng He; Baosheng Li; Xuan Wu; Yu Du; Nianwen Xiang; Shaojun Xu; Lijian Ding (Journal of Environmental Chemical Engineering, 2026)

Bio-based Pickering emulsion coatings for multifunctional, pH-responsive, and biodegradable paper packaging - Xiaotong Shi; Jinsong Wang; Jing Shi; Lijuan Yu; Huining Xiao; Chengcheng Li (Innovative Food Science & Emerging Technologies, 2026)

Multimodal large language models for food safety detection within deep learning frameworks: a review - Haohan Ding; Chengcheng Chen; Xiaodong Song; Guanjun Dong; Haoheng Chen; Haoke Hou; Xiaohui Cui; Wei Yu; David I. Wilsone (Food Chemistry, 2026)

Regenerative human endometrial organoid for functional restoration of endometrial fertility - Chengcheng Zhu; Di Zhang; Xuzhi Chen; Huafei Zhao; Cheng Zhang; Junwen Zhang; Xiaolin Wu; Mohammad Ishraq Zafar; Yu Zhang; Wanwan Xu; Zujian Jin; Xiuying Chen; et al. (Chemical Engineering Journal, 2026)

Metagenomic analysis of fecal microbial communities in dairy goats from different farms - Liang Chengcheng; Zhou Yanduo; Wang Zhebin; Li Jianzhang; Zhu Yangtao; Li Jun; Li Yu; Hashim R. Felemban; Othman Yahya Alyahyawy; Ahmad F. Alhomodi; Fatimah Hadadi; Ali Shaibah; et al. (Protoplasma, 2026)

Multi-media distribution, source apportionment, and risk assessment of legacy and current-use organophosphorus pesticides in typical agricultural watersheds of China - Chengcheng Bu; Limin Ma; Weiwei Zhang; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Qi Wang; Yuefei Ruan; Chong Chen (Water Research, 2026)

Targeted external donor dosing in single-stage partial nitritation-anammox: A carbon-efficient control framework sustaining ultrahigh total nitrogen removal - Chengcheng Lin; Yanxiao Wei; Sha Wu; Jiao Jin; Yangkai Liu; Hong Chen; Hanbo Yu; Mohd Fadhil Md Din; Eli Hendrik Sanjaya; Binquan Wang (Process Safety and Environmental Protection, 2026)

Unraveling metal-organic frameworks impact on resistome and virome dynamics in swine manure anaerobic digestion via metagenomic - Li Zhang; Lan Jiang; Ziyi Zhang; Yufei Wang; Chengcheng Yao; Kunru Yu; Hanxiang Tao; Wei Sun; Xunyang He; Jie Gu; Xun Qian (Journal of Environmental Management, 2026)

Occurrence and differential spatiotemporal distribution of pesticides in a plateau lake basin with intensive vegetable cultivation: A case study in Qilu Lake Basin - Qihui Zhao; Limin Ma; Chengcheng Bu; Yu Hua; Ruolan Jia; Chong Chen (Environmental Research, 2026)

Phoenix Nirvana and rebirth-pyrophilous microbes reconstruct soil microbial communities in a short term post-fire forest - Yu Shi; Xiao Chen; Xiaolei Su; Zhengbo Li; Haixia Qiao; Chengcheng Dong; Kaoping Zhang; Yanjie Liu; Wei Huang (Environmental Research, 2026)

Enhancing urban flood resilience through agent-based modeling of evacuation behaviors - Zeqian Jin; Yicheng Xiong; Chengcheng Yu; Chen Li; Zexin Jin; Xin Ye (Sustainable Cities and Society, 2026)

Tillage combined with straw return increases maize yield and water use by regulating root morphological distribution and nitrogen metabolism in Northeast China - Wen Zhang; Anran Long; Xinjie Ji; Zhanxiang Sun; Ping Tian; Chengcheng Jin; Xiangwei Gong; Ying Jiang; Hua Qi; Haiqiu Yu (Soil and Tillage Research, 2026)

A generic monomer confined strategy for defective UiO-66 synthesis towards enhanced aqueous phosphate removal - Chengcheng Ji; Shaogang Hu; Yifan Bu; Kexin Yi; Chao Li; Shaodong Xie; Shuyan Yu; Fang Zhang; Wulin Yang (Chemical Engineering Journal, 2026)

A city-level assessment framework for low-carbon transition of residential district heating in China - Yanhui Yu; Kairui You; Shicong Zhang; Xinyan Yang; Chengcheng Zhu; Weiguang Cai (Resources, Conservation and Recycling, 2026)

Effectiveness and optimization strategies for contaminant remediation using integrated groundwater circulation well and pump-and-treat methods in heterogeneous aquifer - Zaiyong Zhang; Bin Ran; Yu-Li Wang; Chuanqi Zhang; Pengze Hou; Jiamin Shao; Jingbo Yang; Chengcheng Gong (Process Safety and Environmental Protection, 2026)

Habitat quality assessment and spatiotemporal pattern evolution of the Black-necked Cranes (Grus nigricollis) in Tibet based on the MaxEnt-InVEST model - Jinxun Chen; Zhongbin Wang; Chengcheng Zou; Wanqing Shen; Qiuxiaoxiao Shen; Haiming Li; Enduo Liu; Bo Yu; Huirui Xing (Journal for Nature Conservation, 2026)

Prediction of sea surface pCO2 in the South China Sea using Spatiotemporal Convolutional LSTM model - Shuang Li; Yu Gao; Jiannan Gao; Yaqi Zhao; Peng Hao; Jinbao Song; Chengcheng Yu (Journal of Oceanology and Limnology, 2026)

Stable isotopes reveal the evaporation effects during a drought–flood abrupt alternation period in a semiarid river basin in Inner Mongolia, Northwest China - Jian Luo; Chengcheng Xia; Guoqing Wang; Ruihong Yu; Ruizhong Gao; Xiaomin Liu; Ping Miao; Qiuyu Qiao; Junxi Lin (Journal of Hydrology, 2025)

Sustainable extraction and characterization of type I collagen from tuna skin waste utilizing biocompatible ionic liquid-based aqueous two-phase system - Qianqian Chen; Botao Liang; Xuan Yuan; Xinyi Yu; Chengcheng Li; Lai Wei; Jing Ye; Jiajia Wu; Zhiyuan Dai; Yanbin Lu (Food Hydrocolloids, 2025)

Antibiotics, antibiotic resistance genes, and environmental drivers: Assessment of resistance pollution along the Yangtze River Basin - Chengcheng Bu; Chong Chen; Weiwei Zhang; Ru Zhang; Jinpeng Yu; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Yuefei Ruan; Limin Ma (Environmental Pollution, 2025)

Paramylon biorefinery from Euglena gracilis via recyclable aqueous two-phase system: A sustainable platform for high-content β-1,3-glucan production - Jiajia Wu; Xinyi Yu; Lai Wei; Xuan Yuan; Dongcheng Li; Botao Liang; Chengcheng Li; Zhangchi Chen; Yanbin Lu (Carbohydrate Polymers, 2025)

Soil-air exchange of substituted chlorobenzenes and volatile PFAS at contaminated sites: Impact of environmental factors and development of a fugacity-based model - Weiwei Zhang; Limin Ma; Jinpeng Yu; Chengcheng Bu; Yongzhi Wang; Haoyu Zeng; Yuchen Han (Journal of Hazardous Materials, 2025)

Study on processability, hydration characteristics and solidification mechanism of hazardous elements of high-phosphorus solid waste paste backfill materials - Yandong Han; Lang Liu; Shishan Ruan; Mengbo Zhu; Bo Yu; Huisheng Qu; Chengcheng Shao; Tiantian Li (Journal of Environmental Chemical Engineering, 2025)

A critical review of oxygen supply and control strategies in single-stage partial nitritation-anammox system for autotrophic nitrogen removal from wastewater - Sha Wu; Fei Gao; Chengcheng Lin; Yijie Quan; Yanxiao Wei; Zhihua Liu; Hanbo Yu; Eli Hendrik Sanjaya; Mohd Fadhil Md Din; Hong Chen (Journal of Environmental Chemical Engineering, 2025)

Construction of starch-sodium alginate interpenetrating network as an effective strategy to improve the quality of extruded whole buckwheat noodles during reheating and soaking periods - Tingting Gao; Xiang Xu; Menglan Yu; Fenglian Chen; Chengcheng Gao; Xiao Feng; Zhenjiong Wang; Xiaozhi Tang (Food Structure, 2025)

Exploring genetic variation and fermentation performance of Lactiplantibacillus plantarum strains in tomato juice - Xinyue Hu; Hao Gao; Xiaojie Zang; Mingyang Li; Chengcheng Zhang; Leilei Yu; Fengwei Tian; Qixiao Zhai (Food Bioscience, 2025)

Occurrence and ecological risks of pharmaceuticals along the Yangtze River Basin of China: Insights from target analysis and suspect screening strategy - Chong Chen; Chengcheng Bu; Qi Wang; Yutong Zhang; Shaopeng Xu; Yu Hua; Ruolan Jia; Huiju Lin; Xiaolei Wang; Zhiwei Gan; Xiong Xiong; Limin Ma; et al. (Journal of Hazardous Materials, 2025)

First report of Metschnikowia bicuspidata infection in the oriental river prawn ( Macrobrachium nipponense , de Haan) in China - Yingyue Yu; Songyue You; Chengcheng Feng; Xiaodong Li; Yuenan Xing; Qingbiao Hu; Jie Bao; Hongbo Jiang (Journal of Fish Diseases, 2025)
During breeding, some oriental river prawns ( Macrobrachium nipponense , de Haan), an important aquaculture species in China, exhibit yellowish‐brown body colouration, reduced appetite, and vitality. Diseased prawns revealed characteristic emulsifying disease signs, including whitened musculature, hepatopancreatic tissues, milky haemolymph, and non‐coagulation. The present study investigated the causative agent of M. nipponense infection through isolation, histopathology, molecular sequencing, and infection experiments. The pathogenic strain exhibited distinctive white colonies on Bengal red medium, with microscopic examination confirming the presence of yeast cells. Histopathological analysis revealed prominent pathological alterations and yeast cell infiltration in muscles, hepatopancreas and gills. Additionally, 26S rDNA sequencing of the isolated yeast strain LNMN2022 revealed Metschnikowia bicuspidata (GenBank: OR518659) as the causative agent. This strain exhibited a 98.28% sequence homology with M. bicuspidata LNMB2021 (GenBank: OK094821) and 96.62% with M. bicuspidata LNES0119 (GenBank: OK073903). The pathogenicity test confirmed that M. bicuspidata elicited clinical signs in M. nipponense consistent with those observed in natural populations, and the median lethal concentration was determined to be 3.3 × 10 5 cfu/mL. This study establishes a foundation for further investigations into the host range and epidemiological characteristics of the pathogen M. bicuspidata in aquatic animals and provides an empirical basis for disease management in M. nipponense .

Understanding spatial differences in CO2 emissions between passenger and freight transportation - Yuliang Zhang; Yifan Chen; Yichen Wang; Chengcheng Yu; Xiqun (Michael) Chen; Der-Horng Lee (Transportation Research Part D: Transport and Environment, 2025)

Spatial distribution, phase partitioning, and ecological risk assessment of typical pesticides in Yangtze River Basin - Chengcheng Bu; Chong Chen; Xitong Fu; Weiwei Zhang; Ru Zhang; Yu Hua; Ruolan Jia; Yuefei Ruan; Kenneth Mei Yee Leung; Limin Ma (Journal of Hazardous Materials, 2025)

Seafloor temperature variability in the Zhoushan Archipelago: Patterns and mechanisms - Qiying Wang; Peng Bai; Jingling Yang; Peiliang Li; Chengcheng Yu; Qiong Wu; Zhenxin Ruan; Bo Li (Estuarine, Coastal and Shelf Science, 2025)

Enhancing generalization in non-intrusive thermal comfort prediction through two-stage optimization of attention mechanisms and gender-aware modeling - Xiaofeng Wan; Xiaozheng Xiang; Chengcheng Shan; Zhibin Zheng; Yunjun Yu; Hongwei Tao; Huan Zhang; Hongyang Chen; Dixin Sheng; Jiawen Hu (Building and Environment, 2025)

A novel reinforcement learning framework-based path planning algorithm for unmanned surface vehicle - Jianhui Mou; Bo Shi; Bo Wang; Chengcheng Yu; Yangwei Wang; Fusheng Zhong; Li Zheng; Jian Wang; Junjie Li (Frontiers in Marine Science, 2025)
Unmanned surface vehicles (USVs) nowadays have been widely used in ocean observation missions, helping researchers to monitor climate change, collect environmental data, and observe marine ecosystem processes. However, path planning for USVs often faces several inherent difficulties during ocean observation missions: high dependence on environmental information, long convergence time, and low-quality generated paths. To solve these problems, this article proposes a novel artificial potential field-heuristic reward-averaging deep Q-network (APF-RADQN) framework-based path planning algorithm, aiming at finding optimal paths for USVs. First, the USV path planning is modeled as a Markov decision process (MDP). Second, a comprehensive reward function incorporating artificial potential field (APF) inspiration is designed to guide the USV to reach the target region. Subsequently, an optimized deep neural network with a reward-averaging strategy is constructed to effectively enhance the learning and convergence speed of the algorithm, thus further improving the global search capability and interface performance of USV path planning. In addition, the Bezier curve is applied to make the generated path more feasible. Finally, the effectiveness of the proposed algorithm is verified by comparing it with the DQN, A*, and APF algorithms in simulation experiments. Simulation results demonstrate that the APF-RADQN improves the interface ability and path quality, significantly enhancing the USV navigation safety and ocean observation mission operation efficiency.

Exploring heterogeneity in evacuation decision of urban residents between utility and regret decision rules under a flood hazard - Zeqian Jin; Yichen Wang; Chen Li; Chengcheng Yu; Xin Ye; Jiantao Mu (Sustainable Cities and Society, 2025)

High-frequency detachment of low salinity water from the Changjiang River plume - Shuang Liang; Jingling Yang; Peng Bai; Qiong Wu; Chengcheng Yu; Zhenxin Ruan; Bo Li (Ocean Modelling, 2025)

Seasonal groundwater variations in the coastal plain under intense human activities: Hydrochemical evolution, quality degradation, and health risk assessment - Zhibin Li; Chengpeng Lu; Yong Zhang; Xilin Yu; Qize Gao; Zhenhuan Yuan; Chengcheng Wu; Bo Liu; Longcang Shu (Journal of Environmental Management, 2025)

Spatiotemporal variation and mechanisms of the winter cold water tongue at the top of the Beibu Gulf - Bo Li; Guangji Chen; Peng Bai; Jingling Yang; Chengcheng Yu; Zhenxin Ruan; Qiong Wu; Ying Gao (Ocean Dynamics, 2025)

The mechanisms of lead resistance in Lactiplantibacillus plantarum: Insights from proteomics and metabolomics analyses - Feng Chen; Leilei Yu; Jiani Pan; Chuan Zhang; Chengcheng Zhang; Jianxin Zhao; Narbad Arjan; Wei Chen; Fengwei Tian; Qixiao Zhai (Chemosphere, 2025)

Numerical study of wake-induced vibration of bionic whisker at low mass ratio and Reynolds number - Chengcheng Huang; Weijie Li; Sai Peng; Tingting Tang; Peng Yu (Ocean Engineering, 2025)

Delineate the unknown aquifer geometry and boundary condition using hydraulic tomography - Mpendulo Mangaliso Mtsetfwa; Zaiyong Zhang; Chengcheng Gong; Hong-Ru Lin; Jet-Chau Wen; Yu-Li Wang (Journal of Hydrology, 2025)

Recent progress towards fuels and value-added chemicals through lignin depolymerization - Yu Yin; Chengcheng Suo; Chunhui Ma; Shouxin Liu (Journal of Environmental Chemical Engineering, 2025)

Metabolic interactions between Lactococcus lactis and commercial starter cultures enhances the quality and flavor of fermented milk - Xinyu Guo; Leilei Yu; Yang Liu; Meifang Xiao; Chengcheng Zhang; Jianxin Zhao; Wei Chen; Fengwei Tian; Qixiao Zhai (Food Research International, 2025)

The formation mechanism of volatile and nonvolatile flavor substances in sourdough based on genomics and metabolomics - Xiaoxuan Sun; Zi Ye; Meifang Xiao; Chengcheng Zhang; Min Guo; Jianxin Zhao; Wei Chen; Fengwei Tian; Leilei Yu; Qixiao Zhai (Food Chemistry, 2025)

Exploring a microbiota-targeted dietary strategy for irritable bowel syndrome - Wenxuan Dou; Chengcheng Zhang; Jiaqian Shentu; Haiyan He; Leilei Yu; Fengwei Tian; Jianxin Zhao; Wei Chen; Zhiming Yu; Qixiao Zhai (Food Bioscience, 2025)

Morchella esculenta polysaccharides ameliorate obesity by enriching Bifidobacterium and Bacteroides - Xiaojie Zang; Xing Jin; Bingshu Liu; Chengcheng Zhang; Arjan Narbad; Jianxin Zhao; Wei Chen; Fengwei Tian; Leilei Yu; Qixiao Zhai (Food Bioscience, 2025)

Advance in design techniques and synthesis strategies of porous carbon positive electrodes for aqueous zinc-ion hybrid capacitors - Chengcheng Yu; Xiuxiu Chen; Wenya Gao; Kang Liu; Dingxuan Ma (Chemical Engineering Journal, 2025)

Response of sea-surface partial pressure of CO2 to ENSO events over the Taiwan Strait - Keyu Hu; Qiong Wu; Tianqi Xiong; Bo Li; Peng Bai; Zhenxin Ruan; Chengcheng Yu (Acta Oceanologica Sinica, 2025)

Synergistic Effects of Ocean Background and Tropical Cyclone Characteristics on Tropical Cyclone-Induced Sea Surface Cooling in the Western North Pacific - Rao Rao; Chengcheng Yu; Peng Bai; Bo Li (Journal of Marine Science and Engineering, 2025)
Tropical cyclones (TCs) induce intense mixing in the upper ocean, which significantly impacts sea surface temperature (SST) and marine environment. Previous studies have shown that TCs can cause a decrease in sea surface temperature (DSST), while further research is required to elucidate the factors influencing SST changes. This study employs satellite observations and reanalysis data from the western North Pacific during 2002–2020 to investigate the relationship between DSST and the ocean background state (BG). In addition, by incorporating TC characteristics, we construct indices to explore the synergistic effects of TCs and BG on DSST, enabling a more comprehensive understanding of the mechanisms governing DSST variability. The results indicate that DSST exhibits significant monthly variations, with the maximum DSST in September for coastal regions and in August for offshore regions. Regardless of TC characteristics, when the mixed layer depth (MLD) exceeds 60 m or thermocline depth (TD) exceeds 115 m, it is difficult for the DSST to exceed 1 °C. In both coastal and offshore regions, MLD and TD exhibit moderate negative correlations with DSST, with values around −0.3. When TC characteristics are incorporated, these correlations rise to approximately 0.6, highlighting the importance of jointly considering BG and TC effects in characterizing DSST. The findings of this study provide theoretical support for improving the capability to predict DSST changes before the TC approaches the coast.

Microplastics in groundwater: Environmental fate and possible interactions with coexisting contaminants - Shengfeng Liu; Chengcheng Li; Jochen Bundschuh; Xubo Gao; Xing Gong; Huihui Li; Mengyun Zhu; Ling Yi; Wenxuan Fu; Fengze Yu (Environmental Pollution, 2025)

Co-precipitation enrichment of Pb2+ in water by ball-milling-enhanced diatomite: synergistic effects of crystal structure and surface activity - Fei Jiang; Licheng Ji; Zhongpu Yu; Chengcheng Wei; Feiyue Li (Environmental Geochemistry and Health, 2025)

Karst water quality, source of pollution, and health risk assessment in China - Gongzhe Peng; Xubo Gao; Aqsa Naseem; Yunfei Zhang; Xiangjie Wang; Wenxuan Fu; Fengze Yu; Siyuan Ma; Wanpeng Shi; Ling Yi; Chengcheng Li; Wei Liu; et al. (Science of The Total Environment, 2025)

Implications of the different submerged extent of typical sandbars to local DOM and SDOM during the pre-flood season in the middle reaches of Yangtze River - Haoyang Shi; Hui Guo; Wenjun Yang; Chengcheng Bao; Xinxin Zhu; Sheng Bi; Yu Hu; Ting Li (Journal of Environmental Management, 2025)

Highly efficient Cr-doped cobalt-based catalyst for hydrogen evolution - Fengxin Cao; Qiaoling Li; Boya Shan; Zhiwei Qi; Chenyu Zhang; Chengcheng Yu (Journal of Environmental Chemical Engineering, 2025)

Responses of soil greenhouse gas fluxes to land management in forests and grasslands: A global meta-analysis - Huanhuan Liu; Yuqi Miao; Yu Chen; Yifan Shen; Yongfa You; Zhuonan Wang; Chengcheng Gang (Science of The Total Environment, 2025)

Latilactobacillus sakei CCFM1267 enhances fermentation and probiotic properties in fermented milk: A focus on metabolomics and physicochemical analysis - Yuxuan Xia; Xing Jin; Meifang Xiao; Zi Ye; Chengcheng Zhang; Jianxin Zhao; Wei Chen; Fengwei Tian; Leilei Yu; Qixiao Zhai (Food Bioscience, 2025)

Enhancing groundwater remediation efficiency through integrating Pump-and-Treat system and groundwater circulation well - Zaiyong Zhang; Bin Ran; Chengcheng Gong; Ni Yan; Jingbo Yang; Chunqiang Shen; Yu-Li Wang (Process Safety and Environmental Protection, 2025)

Parameterization of Langmuir circulation under geostrophic effects using the data-driven approach - Yu Gao; Jinbao Song; Shuang Li; Chengcheng Yu; Peng Hao (Progress in Oceanography, 2025)

Why they are experiencing long-time commuting: A gendered analysis across occupational, family, and spatial dimensions - Nixuan Ye; Chao Yang; Chengcheng Yu (Journal of Transport Geography, 2025)

pH-responsive fiber membrane with high flux and photocatalytic performance for oily wastewater - Jie Wang; Bingyan Yu; Keru Hou; Yating Ji; Xiaoyan Li; Chengcheng Li; Chengjian Yao; Zaisheng Cai (Journal of Environmental Chemical Engineering, 2025)

TriangularSORT: A Deep Learning Approach for Ship Wake Detection and Tracking - Chengcheng Yu; Yanmei Zhang (Journal of Marine Science and Engineering, 2025)
Ship wake detection and tracking are of paramount importance for ensuring maritime safety, conducting effective ocean monitoring, and managing maritime affairs, among other critical applications. This paper introduces a novel approach for ship tracking and wake detection utilizing advanced computational techniques, particularly the TriangularSORT algorithm for monitoring vessels. This method enhances effective ship tracking by closely associating the vertices of the triangular wake with the coordinates of the ship. Furthermore, this paper integrates the triangular IoU and attention mechanism, introducing the Triangular Attention Mechanism. This mechanism guides the model’s focus to key areas of the image by defining triangular points on the feature map, thereby enhancing the model’s ability to recognize and analyze local features in visual tasks. Experimental results demonstrate that the proposed method significantly improves the performance and accuracy of models in object detection and tracking tasks.

Exploring Core fermentation microorganisms, flavor compounds, and metabolic pathways in fermented Rice and wheat foods - Xiaoxuan Sun; Leilei Yu; Meifang Xiao; Chengcheng Zhang; Jianxing Zhao; Arjan Narbad; Wei Chen; Qixiao Zhai; Fengwei Tian (Food Chemistry, 2025)

Ampelopsis grossedentata tea polysaccharide alleviates D-galactose-induced aging in mice and regulates gut microbiota - Jiani Pan; Feng Chen; Leilei Yu; Kan Hong; Zi Ye; Qingsong Zhang; Chengcheng Zhang; Jianxin Zhao; Qixiao Zhai; Fengwei Tian (Food Bioscience, 2025)

Bifunctional role of mechanical catalysis approach accelerates CO2 hydrogenation under low temperature - Keran Lv; Wenpeng Lv; Cheng Liu; Chengcheng Liu; Michael Claeys; Guoqing Ren; Weiqiao Deng; Tie Yu (Chemical Engineering Journal, 2025)

Unraveling the role of freight facility development in the dynamics of gentrification - Zhengtao Qin; Chengcheng Yu; Haocheng Lin; Chao Yang; Quan Yuan (Transportation Research Part D: Transport and Environment, 2024)

Effects of temperature, relative humidity and soil organic carbon content on soil-air partitioning coefficients of volatile PFAS - Weiwei Zhang; Limin Ma; Songsong Chen; Chong Chen; Chengcheng Bu; Jinpeng Yu; Ru Zhang; Yongzhi Wang; Haoyu Zeng; Yuchen Han (Science of The Total Environment, 2024)

Step-wise reproductive toxicities of imidazolium- and pyridinium-based ionic liquids on Caenorhabditis elegans - Jing Zhang; Chengcheng Lv; Zhenyang Yu; Yangyuan Zhou (Journal of Hazardous Materials, 2024)

Differential characteristics of chemical composition, fermentation metabolites and antioxidant effects of polysaccharides from Eurotium Cristatum and Fu-brick tea - Zhengwei Tan; Pinglian Yu; Haoyan Zhu; Jiaobei Gao; Ning Han; Chengcheng Yang; Zhuo Shen; Chang Gao; Xingbin Yang (Food Chemistry, 2024)

The soil-air interfacial migration process of volatile PFAS at the contaminated sites: Evidence from stable carbon isotopes with CSIA - Zhang Weiwei; Chen Songsong; Wang Yongzhi; Zhang Ru; Bu Chengcheng; Yu Jinpeng; Ma Limin (Environmental Pollution, 2024)

Spatiotemporally non-stationary evolution of groundwater levels in Poyang Lake Basin driven by meteorological and hydrological factors - Yu Liu; Chengpeng Lu; Baozhong Qiu; Jianliang Wang; Jing Chen; Yong Zhang; Chengcheng Wu; Bo Liu; Longcang Shu (Science of The Total Environment, 2024)

Multi-omics integration analysis: Tools and applications in environmental toxicology - Chengcheng Shi; Lin Cheng; Ying Yu; Shuangshuang Chen; Yubing Dai; Jiajia Yang; Haijun Zhang; Jiping Chen; Ningbo Geng (Environmental Pollution, 2024)

Green chemistry closed-loop: Photocatalytic cleavage lignin β-O-4 bond utilizing visible light by Bi2O3/Bi2WO6 in deep eutectic solvent at room temperature - Chengcheng Suo; Jintao Yu; Jifang Zhang; Wei Li; Sha Luo; Chunhui Ma; Shouxin Liu (Biomass and Bioenergy, 2024)

Dynamic changes on sensory property, nutritional quality and metabolic profiles of green kernel black beans during Eurotium cristatum-based solid-state fermentation - Yuanyuan Zhang; Bangran Qi; Qiannan Li; Chengcheng Yang; Pinglian Yu; Xingbin Yang; Ting Li (Food Chemistry, 2024)

Factors involved in the abundant dominance of Bifidobacterium longum within the genus in the human gut - Liuruolan Li; Chengcheng Zhang; Bingshu Liu; Fengwei Tian; Leilei Yu; Wei Chen; Qixiao Zhai (Food Bioscience, 2024)

Hyaluronic acid modulates gut microbiota and metabolites relieving inflammation: A molecular weight-dependent study - Chuan Zhang; Botao Wang; Leilei Yu; Ruohan Zhao; Qingsong Zhang; Chengcheng Zhang; Shumao Cui; Jianxin Zhao; Arjan Narbad; Wei Chen; Fengwei Tian; Qixiao Zhai (Science Bulletin, 2024)

Effects of fatty acids and glycerides on the structure, cooking quality, and in vitro starch digestibility of extruded buckwheat noodles - Menglan Yu; Shuyi Zhang; Peiqi Tang; Linghan Meng; Weiwei Cheng; Chengcheng Gao; Di Wu; Xiao Feng; Zhenjiong Wang; Xiaozhi Tang (Food Research International, 2024)

Organofluorinated Ag/2D diamond nanocomposites achieve simultaneously ultra-low friction and wear in self-lubricating epoxy - Qingzhao Cai; Chengcheng Jiao; Junhao Wu; Shanqin Ge; Wei Li; Long Chen; Genxiang Gong; Jiamin Yu; Yaokang lv; Jinhong Yu; Kazuhito Nishimura; Nan Jiang; et al. (Chemical Engineering Journal, 2024)

An amorphous SnP2O7-carbon architecture with enhanced rate and cyclic stability for sodium-ion batteries - Mei Ma; Binhao Yu; Yongmei Sun; Mingzhu Zhu; Wenfang Cui; Chengcheng Shi (Chemical Engineering Journal, 2024)

Indicative bacterial cellulose films incorporated with curcumin-embedded Pickering emulsions: Preparation, antibacterial performance, and mechanism - Wanting Miao; Ruihan Gu; Xiaotong Shi; Junze Zhang; Lijuan Yu; Huining Xiao; Chengcheng Li (Chemical Engineering Journal, 2024)

Water-dispersible macromolecular antioxidants for toughening and strengthening cellulose membranes - Jie Wang; Wei Gao; Yu Jin; Wangmao Tian; Yutao Zhang; Chengcheng Hu; Baoxia Wang; Shuqi Dong; Liang Yuan (Carbohydrate Polymers, 2024)

Galla Turcica alleviates gingiva inflammation and alveolar bone resorption via regulating Th1/Th17 in a mouse model of periodontitis - Yakun Han; Chengcheng Yu; Yan Yu (Advances in Traditional Medicine, 2024)

Effect of different concentrations of carbonate on growth performance, intestinal health and hepatic lipid metabolism of Crucian carp - Xin-yu Lei; Xue Cao; Jia Sun; Chengcheng Bi; Xin Wang; Yue-hong Li (Aquaculture, 2024)

Creating most needed customized bus services: A collaborative analysis of user-route dynamics - Chengcheng Yu; Haocheng Lin; Yitong Chen; Chao Yang; Ailing Yin; Quan Yuan (Transportation Research Part D: Transport and Environment, 2024)

Deficiency of betaine-homocysteine methyltransferase activates glucose-6-phosphate dehydrogenase (G6PD) by decreasing arginine methylation of G6PD in hepatocellular carcinogenesis - Jie Gao; Xiaoyi Shi; Yaohui Sun; Xudong Liu; Feng Zhang; Chengcheng Shi; Xiao Yu; Zhiping Yan; Long Liu; Shizhe Yu; Jiacheng Zhang; Xiaodan Zhang; et al. (Science China Life Sciences, 2024)

The impact of tropical cyclone outer size on ocean surface responses - Zhenxin Ruan; Bo Li; Chengcheng Yu; Ruibin Ding; Peng Bai; Qiong Wu (Frontiers in Marine Science, 2024)
We used daily sea surface temperature (SST) data and hourly drifter data to investigate ocean responses to tropical cyclone (TC) intensity and outer size (wind radius of 34 kt, or R34) in the Northwest Pacific. Results showed that SST cooling is more sensitive to TC R34 than to TC intensity; namely, TCs with a larger R34 cause stronger SST cooling regardless of their intensity. TCs with an R34 ≥125 nmi could cool SST 0.9°C more than TCs with an R34<125 nmi. Drifter data indicated that TCs generate a large current with near-inertial periods. The filtered near-inertial currents were used to calculate the time series of near-inertial kinetic energy E f , and found that TCs with a larger R34 will trigger stronger E f . Further analysis revealed that the non-dimensional storm speed S , which is defined as the ratio of the local near-inertial period to the residence time of the TC, is correlated closely with the amplitude of SST cooling when R34 is used to quantify the scale of the TC. Most TCs have a residence time smaller than the local near-inertial period, and therefore, TCs with a large R34 have longer residence times and are closer to the local near-inertial period, which is favorable for stronger SST and current responses. This impact of TC outer size on the surface ocean response implies the critical role of TC outer size in ocean processes under a TC background.

Impacts and influencing pathways of urbanization on carbon–water-energy-food nexus across Chinese cities - Chenggang Li; Yong Liu; Zhenci Xu; Gang Zhao; Youhui Bao; Chengcheng Cai; Yu Lu; Yufeng Mao; Alexander Boxuan Wang; Liang Wu (Environment, Development and Sustainability, 2024)
Food, water, energy and carbon (F-W-E-C), as important factors of urban development, have synergistic effects and trade-off effects with each other. Scientifically assessing the impact of urbanization on the F-W-E-C nexus is beneficial to optimize the urban development layout and achieve the sustainable urban development. Nevertheless, extant studies have not evaluated the impact and influencing pathways of urbanization on the F-W-E-C nexus. In this study, the Coupling Coordination Degree Model is used to explore the F-W-E-C nexus of 252 prefecture-level cities in China. The panel data model and mediating effect model are utilized to study the impact of urbanization on the F-W-E-C nexus and the impact pathways. This study finds that the F-W-E-C nexus across Chinese cities is weak trade-off. The urbanization promotes the synergy of F-W-E-C. The positive impact is greater in the central cities than in the eastern and western cities, and is greater in medium-sized cities than in small cities, large cities and above. The technological progress is an important pathway of urbanization impacting the F-W-E-C nexus, and assists urbanization to generate a positive influence on the F-W-E-C nexus. This research has implications for promoting a systematic, orderly, and rational coordination development of F-W-E-C and for sustainable urbanization development in China and the world.

Soliton solution, breather solution and rational wave solution for the coupled macroscopic fluctuation theory equation in the optimal path of the process - Li Li; Chengcheng Fan; Fajun Yu (Wave Motion, 2024)

Integrated strategies for road transportation-related multi-pollutant control: A cross-departmental policy mix - Chengcheng Yu; Zhengtao Qin; Yougeng Lu; Haocheng Lin; Chao Yang; Quan Yuan; Qingyang Wu (Transportation Research Part D: Transport and Environment, 2024)

In situ cleaning of foulants by gas scouring on the membrane-electrode in an electro-membrane bioreactor - Boyang Yu; Chengcheng Xie; Chenghai Lu; Zhibin Chen; Jiayu Tian; Chengzhi Hu (Bioresource Technology, 2024)

Sulfate-reducing bacteria (SRB) mediated carbonate dissolution and arsenic release: Behavior and mechanisms - Yu Jiang; Xubo Gao; Xinwen Yang; Peili Gong; Zhendong Pan; Ling Yi; Siyuan Ma; Chengcheng Li; Shuqiong Kong; Yanxin Wang (Science of The Total Environment, 2024)

Dynamic causes contribute to the increasing trend of red tides in the east China sea during 2020–2022 - Yu Gao; Peng Hao; Zilu Wei; Shuang Li; Jinbao Song; Chengcheng Yu (Marine Environmental Research, 2024)

Genome-wide characterization, transcriptome profiling, and functional analysis of the ALMT gene family in Medicago for aluminum resistance - Dehui Jin; Jinlong Chen; Yumeng Kang; Fang Yang; Dongwen Yu; Xiaoqing Liu; Chengcheng Yan; Zhenfei Guo; Yang Zhang (Journal of Plant Physiology, 2024)

Construction of P-doped high efficiency hydrogen evolution catalyst - Yao Zhang; Yan Zhang; Wenjing Wang; Fengxin Cao; Zhikang Yang; Qiaoling Li; Chengcheng Yu (Journal of Environmental Chemical Engineering, 2024)

In vitro batch fermentation demonstrates variations in the regulation of gut microbiota and metabolic functions by β-glucans of differing structures - Yuhang Gao; Leilei Yu; Zi Ye; Chuan Zhang; Yuhong Gong; Qingsong Zhang; Chengcheng Zhang; Jianxin Zhao; Arjan Narbad; Wei Chen; Qixiao Zhai; Fengwei Tian (Food Research International, 2024)

Preparation of O-g-C3N4 nanowires/Bi2O2CO3 porous plate composite photocatalysts for the efficient degradation of tetracycline hydrochloride in wastewater - Lei Zhu; Xiang Ge; Hang Yu; Chengcheng Li; Qirui Wang; Wenlong Zhang; Xun Wang; Xian Liu (Environmental Research, 2024)

Distribution patterns and origins of organophosphate esters in soils from different climate systems on the Tibetan Plateau - Chengcheng Zhu; Zhigang Yu; Yifan Chen; Yiyao Pan; Ruiqiang Yang; Qinghua Zhang; Guibin Jiang (Environmental Pollution, 2024)

Preparation of geopolymer based on municipal solid waste incineration fly ash-phosphorus slag and its function for solidification of heavy metals - An Sai; Wang Baomin; Chen Wenxiu; Yu Ze; Fan Chengcheng (Waste Management, 2024)

Enhancing predictions of remedial reagent transport via a vertical groundwater circulation well with high-resolution aquifer characterization - Zaiyong Zhang; Jingbo Yang; Chengcheng Gong; Wenke Wang; Bin Ran; Guangqi Wang; Qian Zhang; Yu-Li Wang (Science of The Total Environment, 2024)

Metabolomic and microbiome profiling reveals the anti-Pb effect of Lactiplantibacillus plantarum - Yuhang Gao; Leilei Yu; Hui Duan; Yaqi Yu; Chengcheng Zhang; Arjan Narbad; Wei Chen; Fengwei Tian; Qixiao Zhai (Food Bioscience, 2024)

Medium optimization and dust suppression performance analysis of microbial-based dust suppressant compound by response surface curve method - Xiangming Hu; Zhiyuan Yang; Yanyun Zhao; Yue Dong; Chengcheng Wang; Linlin Zhang; Yiyun Yu; Kai Wu; Liyan Ren (Environmental Science and Pollution Research, 2024)

Characteristics of dew/hoar frost from Artemisia ordosica and bare soil based on weighing lysimeters in a semi-arid region - Bin Ran; Chengcheng Gong; Yu-Li Wang; Zaiyong Zhang; Wenke Wang; Jingbo Yang; Da Xu (Journal of Hydrology, 2024)

The transport and distribution of novel brominated flame retardants (NBFRs) and organophosphate esters (OPEs) in soils and moss along mountain valleys in the Himalayas - Yu Chen; Hao Xian; Chengcheng Zhu; Yingming Li; Zhiguo Pei; Ruiqiang Yang; Qinghua Zhang; Guibin Jiang (Journal of Hazardous Materials, 2024)

Genetic diversity and population structure of different Schisandraceae accessions by EST-SSR markers - Guangli Shi; Binhong Zhu; Dan Sun; Zhenxing Wang; Jun Ai; Jiaqi Geng; Xiang Li; Miao Yu; Chengcheng Zhao; Xiyu Zhang (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Green catalysis for the production of n-butyl acetate over phosphotungstic acid-encapsulated metal-organic framework UiO-67 catalyst: Catalyst preparation, characterization and reaction kinetics - Tianlin Ma; Chengcheng Song; Hongliang Chen; Manyun Yin; Chunyang Su; Ningfei Guo; Yang Yao; Mingming Yu; Yujie Wang; Gangling Chen; Zhi Yun (Sustainable Chemistry and Pharmacy, 2024)

Identification of Increased Grain Length 1 (IGL1), a novel gene encoded by a major QTL for modulating grain length in rice - Jiayu Niu; Fei Wang; Chengcheng Yang; Qiwen Ye; Jingxian Huang; Yumei La; Qianqian Wang; Jie Dai; Tiange Hu; Liran Sang; Peijiang Zhang; Yu Zou; et al. (Theoretical and Applied Genetics, 2024)

Response differences of gut microbiota in oligofructose and inulin are determined by the initial gut Bacteroides/Bifidobacterium ratios - Pingping Yin; Ting Du; Shanrong Yi; Chengcheng Zhang; Leilei Yu; Fengwei Tian; Wei Chen; Qixiao Zhai (Food Research International, 2023)

Traffic volume and road network structure: Revealing transportation-related factors on PM2.5 concentrations - Chengcheng Yu; Yongqi Deng; Zhengtao Qin; Chao Yang; Quan Yuan (Transportation Research Part D: Transport and Environment, 2023)

Effect of surfactant on urease-producing flora from waste activated sludge using microbially induced calcite precipitation technology to suppress coal dust - Yanyun Zhao; Wenhao Liu; Xiangming Hu; Xiao Li; Chengcheng Wang; Yiyun Yu; Jing Zhang (Environmental Research, 2023)

Stable isotopes reveal the surface water-groundwater interaction and variation in young water fraction in an urbanized river zone - Chengcheng Xia; Yujie Liu; Yuchuan Meng; Guodong Liu; Xiaohua Huang; Yu Chen; Ke Chen (Urban Climate, 2023)

Divergent trends of changes in annual mean and summer temperature in southwestern China during the Holocene - Can Zhang; Cheng Zhao; Shi-Yong Yu; Bin Xue; Xiangdong Yang; Yanling Li; Chengcheng Leng; Jun Cheng; Ji Shen (Global and Planetary Change, 2023)

Meta-analysis reveals different functional characteristics of human gut Bifidobacteria associated with habitual diet - Pingping Yin; Chengcheng Zhang; Ting Du; Shanrong Yi; Leilei Yu; Fengwei Tian; Wei Chen; Qixiao Zhai (Food Research International, 2023)

Immobilized horseradish peroxidase on boric acid modified polyoxometalate molecularly imprinted polymer for biocatalytic degradation of phenol in wastewater: Optimized immobilization, degradation and toxicity assessment - Xue Yang; Chengcheng Jin; Kai Yu; Miaomiao Tian (Environmental Research, 2023)

Boosting photocatalytic activity of CdLa2S4/ZnIn2S4 S-scheme heterojunctions with spatial separation of photoexcited carries - Meng Dai; Huijun Yu; Wenhan Chen; Kongyu-Ang Qu; Dong Zhai; Chengcheng Liu; Shan Zhao; Shuguang Wang; Zuoli He (Chemical Engineering Journal, 2023)

Phosphorus doping significantly enhanced the catalytic performance of cobalt-single-atom catalyst for peroxymonosulfate activation and contaminants degradation - Ning Chen; Yu Zeng; Tai Li; Peixin Cui; Dionysios D. Dionysiou; Xiaolei Wang; Cun Liu; Guodong Fang; Chengcheng Ding; Yuan Zhao; Juan Gao; Yujun Wang; et al. (Journal of Hazardous Materials, 2023)

MAPK family genes' influences on myogenesis in cattle: Genome-wide analysis and identification - Bingzhi Li; Jianfang Wang; Sayed Haidar Abbas Raza; Sihu Wang; Chengcheng Liang; Wenzheng Zhang; Shengchen Yu; Mujahid Ali Shah; Waleed Al Abdulmonem; Yousef Mesfer Alharbi; Abdullah S.M. Aljohani; Sameer D. Pant; et al. (Research in Veterinary Science, 2023)

Quinoa protein Pickering emulsion: A promising cryoprotectant to enhance the freeze-thaw stability of fish myofibril gels - Kaiyue Cen; Caoxing Huang; Xi Yu; Chengcheng Gao; Yuling Yang; Xiaozhi Tang; Xiao Feng (Food Chemistry, 2023)

The cascade regulation of small RNA and quorum sensing system: Focusing on biofilm formation of foodborne pathogens in food industry - Ying Zhang; Qingping Wu; Stephen Forsythe; Chengcheng Liu; Nuo Chen; Yangfu Li; Jumei Zhang; Juan Wang; Yu Ding (Food Bioscience, 2023)

Removal of Tetracycline Hydrochloride by Ball-Milled Mulberry Biochar - Zhongpu Yu; Licheng Ji; Yihan Zuo; Feiyan Zhang; Chengcheng Wei; Fei Jiang; Xianju Fu; Wenge Wu; Jian Du; Chengxia Chen; Feiyue Li (Water, Air, & Soil Pollution, 2023)

An evaluation of the impact of traffic on the distribution of PAHs and oxygenated PAHs in the soils and moss of the southeast Tibetan Plateau - Lijia Wei; Zhigang Yu; Chengcheng Zhu; Yu Chen; Zhiguo Pei; Yingming Li; Ruiqiang Yang; Qinghua Zhang; Guibin Jiang (Science of The Total Environment, 2023)

Green or not? Environmental challenges from photovoltaic technology - Haiyan Zhang; Zhigang Yu; Chengcheng Zhu; Ruiqiang Yang; Bing Yan; Guibin Jiang (Environmental Pollution, 2023)

Dynamics of global dryland vegetation were more sensitive to soil moisture: Evidence from multiple vegetation indices - Huanhuan Liu; Yue Liu; Yu Chen; Mengen Fan; Yin Chen; Chengcheng Gang; Yongfa You; Zhuonan Wang (Agricultural and Forest Meteorology, 2023)

Increased Soluble Epoxide Hydrolase Activity Positively Correlates with Mortality in Heart Failure Patients with Preserved Ejection Fraction: Evidence from Metabolomics - Liyuan Peng; Ziping Song; Chengcheng Zhao; Kudusi Abuduwufuer; Yanwen Wang; Zheng Wen; Li Ni; Chenze Li; Ying Yu; Yi Zhu; Hualiang Jiang; Jinshan Shen; et al. (Phenomics, 2023)

Spatiotemporal Dynamics of the Molecular Expression Pattern and Intercellular Interactions in the Glial Scar Response to Spinal Cord Injury - Leilei Gong; Yun Gu; Xiaoxiao Han; Chengcheng Luan; Chang Liu; Xinghui Wang; Yufeng Sun; Mengru Zheng; Mengya Fang; Shuhai Yang; Lai Xu; Hualin Sun; et al. (Neuroscience Bulletin, 2023)
Nerve regeneration in adult mammalian spinal cord is poor because of the lack of intrinsic regeneration of neurons and extrinsic factors – the glial scar is triggered by injury and inhibits or promotes regeneration. Recent technological advances in spatial transcriptomics (ST) provide a unique opportunity to decipher most genes systematically throughout scar formation, which remains poorly understood. Here, we first constructed the tissue-wide gene expression patterns of mouse spinal cords over the course of scar formation using ST after spinal cord injury from 32 samples. Locally, we profiled gene expression gradients from the leading edge to the core of the scar areas to further understand the scar microenvironment, such as neurotransmitter disorders, activation of the pro-inflammatory response, neurotoxic saturated lipids, angiogenesis, obstructed axon extension, and extracellular structure re-organization. In addition, we described 21 cell transcriptional states during scar formation and delineated the origins, functional diversity, and possible trajectories of subpopulations of fibroblasts, glia, and immune cells. Specifically, we found some regulators in special cell types, such as Thbs1 and Col1a2 in macrophages, CD36 and Postn in fibroblasts, Plxnb2 and Nxpe3 in microglia, Clu in astrocytes, and CD74 in oligodendrocytes. Furthermore, salvianolic acid B, a blood–brain barrier permeation and CD36 inhibitor, was administered after surgery and found to remedy fibrosis. Subsequently, we described the extent of the scar boundary and profiled the bidirectional ligand-receptor interactions at the neighboring cluster boundary, contributing to maintain scar architecture during gliosis and fibrosis, and found that GPR37L1_PSAP, and GPR37_PSAP were the most significant gene-pairs among microglia, fibroblasts, and astrocytes. Last, we quantified the fraction of scar-resident cells and proposed four possible phases of scar formation: macrophage infiltration, proliferation and differentiation of scar-resident cells, scar emergence, and scar stationary. Together, these profiles delineated the spatial heterogeneity of the scar, confirmed the previous concepts about scar architecture, provided some new clues for scar formation, and served as a valuable resource for the treatment of central nervous system injury.

Correction to: Increased Soluble Epoxide Hydrolase Activity Positively Correlates with Mortality in Heart Failure Patients with Preserved Ejection Fraction: Evidence from Metabolomics - Liyuan Peng; Ziping Song; Chengcheng Zhao; Kudusi Abuduwufuer; Yanwen Wang; Zheng Wen; Li Ni; Chenze Li; Ying Yu; Yi Zhu; Hualiang Jiang; Jinshan Shen; et al. (Phenomics, 2022)

Enhanced Adsorption of Methylene Blue Using H2O2-Modified Hydrochar - Chengcheng Wei; Feiyue Li; Zhongpu Yu; Licheng Ji; Fei Jiang; Chengxia Chen; Jing Yang (Water, Air, & Soil Pollution, 2022)

A Prediction Model of Significant Wave Height in the South China Sea Based on Attention Mechanism - Peng Hao; Shuang Li; Chengcheng Yu; Gengkun Wu (Frontiers in Marine Science, 2022)
Significant wave height (SWH) prediction plays an important role in marine engineering fields such as fishery, exploration, power generation, and ocean transportation. Traditional SWH prediction methods based on numerical models cannot achieve high accuracy. In addition, the current SWH prediction methods are largely limited to single-point SWH prediction, without considering regional SWH prediction. In order to explore a new SWH prediction method, this paper proposes a deep neural network model for regional SWH prediction based on the attention mechanism, namely CBA-Net. In this study, the wind and wave height of the ERA5 data set in the South China Sea from 2011 to 2018 were used as input features to train the model to evaluate the SWH prediction performance at 1 h, 12 h, and 24 h. The results show that the single use of a convolutional neural network cannot accurately predict SWH. After adding the Bi-LSTM layer and attention mechanism, the prediction of SWH is greatly improved. In the 1 h SWH prediction using CBA-Net, SARMSE, SAMAPE, SACC are 0.299, 0.136, 0.971 respectively. Compared with the CNN + Bi-LSTM method that does not use the attention mechanism, SARMSE and SAMAPE are reduced by 43.4% and 48.7%, respectively, while SACC is increased by 5%. In the 12 h SWH prediction, SARMSE, SAMAPE, and SACC of CBA-Net are 0.379, 0.177, 0.954 respectively. In the 24 h SWH prediction, SARMSE, SAMAPE, and SACC of CBA-Net are 0.500, 0.236, 0.912 respectively. Although with the increase of prediction time, the performance is slightly lower than that of 12 h, the prediction error is still maintained at a small level, which is still better than other methods.

The effects of temperature, pressure and concentration on the hydraulic conductivity of deep groundwater-bearing layers - Yang Xie; Guodong Liu; Yu Chen; Mengxi Yang; Chengcheng Xia; Xiaohua Huang (Hydrogeology Journal, 2022)

Genetic diversity among a collection of bitter gourd (Momordica charantia L.) cultivars - Junjie Cui; Yinhui Zhou; Jian Zhong; Chengcheng Feng; Yu Hong; Kailin Hu; Yi Cao (Genetic Resources and Crop Evolution, 2022)

CLTS-Net: A More Accurate and Universal Method for the Long-Term Prediction of Significant Wave Height - Shuang Li; Peng Hao; Chengcheng Yu; Gengkun Wu (Journal of Marine Science and Engineering, 2021)
Significant wave height (SWH) prediction plays an important role in marine engineering areas such as fishery, exploration, power generation, and ocean transportation. For long-term forecasting of a specific location, classical numerical model wave height forecasting methods often require detailed climatic data and incur considerable calculation costs, which are often impractical in emergencies. In addition, how to capture and use the dynamic correlation between multiple variables is also a major research challenge for multivariate SWH prediction. To explore a new method for predicting SWH, this paper proposes a deep neural network model for multivariate time series SWH prediction—namely, CLTS-Net. In this study, the sea surface wind and wave height in the ERA5 dataset of the relevant points P1, P2, and P3 from 2011 to 2018 were used as input information to train the model and evaluate the model’s SWH prediction performance. The results show that the correlation coefficients (R) of CLTS-Net are 0.99 and 0.99, respectively, in the 24 h and 48 h SWH forecasts at point P1 along the coast. Compared with the current mainstream artificial intelligence-based SWH solutions, it is much higher than ANN (0.79, 0.70), RNN (0.82, 0.83), LSTM (0.93, 0.91), and Bi-LSTM (0.95, 0.94). Point P3 is located in the deep sea. In the 24 h and 48 h SWH forecasts, the R of CLTS-Net is 0.97 and 0.98, respectively, which are much higher than ANN (0.71, 0.72), RNN (0.85, 0.78), LSTM (0.85, 0.78), and Bi-LSTM (0.93, 0.93). Especially in the 72 h SWH forecast, when other methods have too large errors and have lost their practical application value, the R of CLTS-Net at P1, P2, and P3 can still reach 0.81, 0.71, and 0.98. The results also show that CLTS-Net can capture the short-term and long-term dependencies of data, so as to accurately predict long-term SWH, and has wide applicability in different sea areas.

Sea Surface Heights and Marine Gravity Determined from SARAL/AltiKa Ka-band Altimeter Over South China Sea - Chengcheng Zhu; Xin Liu; Jinyun Guo; Shengwen Yu; Yupeng Niu; Jiajia Yuan; Zhen Li; Yonggang Gao (Pure and Applied Geophysics, 2021)

A siphon drainage method for stabilizing bank slopes under water drawdown condition - Yang Yu; Chengcheng Lv; Dongfei Wang; Qi Ge; Hongyue Sun; Yuequan Shang (Natural Hazards, 2021)

Marine gravity determined from multi-satellite GM/ERM altimeter data over the South China Sea: SCSGA V1.0 - Chengcheng Zhu; Jinyun Guo; Jinyao Gao; Xin Liu; Cheinway Hwang; Shengwen Yu; Jiajia Yuan; Bing Ji; Bin Guan (Journal of Geodesy, 2020)

Establishment and application of a multiplex PCR assay for detection of Rhizoctonia cerealis, Bipolaris sorokiniana, and Fusarium spp. in winter wheat - Xiaofeng Sun; Li Zhang; Chengcheng Meng; Dezhen Zhang; Nana Xu; Jinfeng Yu (Journal of Plant Pathology, 2020)

Quality control of marine big data—a case study of real-time observation station data in Qingdao - Chengcheng Qian; Aichao Liu; Rui Huang; Qingrong Liu; Wenkun Xu; Shan Zhong; Le Yu (Journal of Oceanology and Limnology, 2019)

Lacustrine Basin Fills in an Early Cretaceous Half-Graben, Jiuquan Basin, NW China: Controlling Factors and Implications for Source Rock Depositional Processes and Heterogeneity - Chengcheng Zhang; Hua Wang; Si Chen; Junjie Yu; Yuantao Liao; Zongsheng Lu; Jun Wei (Journal of Earth Science, 2019)

A national assessment of the effect of intensive agro-land use practices on nonpoint source pollution using emission scenarios and geo-spatial data - Dong Zhuo; Liming Liu; Huirong Yu; Chengcheng Yuan (Environmental Science and Pollution Research, 2018)

MiR-126 Affects Brain-Heart Interaction after Cerebral Ischemic Stroke - Jieli Chen; Chengcheng Cui; Xiaoping Yang; Jiang Xu; Poornima Venkat; Alex Zacharek; Peng Yu; Michael Chopp (Translational Stroke Research, 2017)

Cytoplasmic expression of a thermostable invertase from Thermotoga maritima in Lactococcus lactis - Han Bin Pek; Pei Yu Lim; Chengcheng Liu; Dong-Yup Lee; Xuezhi Bi; Fong Tian Wong; Dave Siak-Wei Ow (Biotechnology Letters, 2017)

Effect of dietary probiotic supplementation on intestinal microbiota and physiological conditions of Nile tilapia (Oreochromis niloticus) under waterborne cadmium exposure - Qixiao Zhai; Leilei Yu; Tianqi Li; Jiamin Zhu; Chengcheng Zhang; Jianxin Zhao; Hao Zhang; Wei Chen (Antonie van Leeuwenhoek, 2017)

Simple Linear Modeling Approach for Linking Hydrological Model Parameters to the Physical Features of a River Basin - Chengcheng Huang; Guoqiang Wang; Xiaogu Zheng; Jingshan Yu; Xinyi Xu (Water Resources Management, 2015)

High dose of extracellular ATP switched autophagy to apoptosis in anchorage-dependent and anchorage-independent hepatoma cells - Qing Wei; Ying Zhang; Lei Sun; Xiaoqing Jia; Wanwan Huai; Chengcheng Yu; Zhengkun Wan; Lihui Han (Purinergic Signalling, 2013)

Estimation of the North–South Transect of Eastern China forest biomass using remote sensing and forest inventory data - Yanhua Gao; Xinxin Liu; Chengcheng Min; Honglin He; Guirui Yu; Min Liu; Xudong Zhu; Qiao Wang (International Journal of Remote Sensing, 2013)

Synthesis, Crystal Structure and Photoluminescence of a Cyclometalated Iridium(III) Coumarin Complex - Tianzhi Yu; Chengcheng Zhang; Yuling Zhao; ShaoQiang Guo; Peng Liu; Wentao Li; Duowang Fan (Journal of Fluorescence, 2013)

Characterization of the Pearl Oyster (Pinctada martensii) Mantle Transcriptome Unravels Biomineralization Genes - Yaohua Shi; Chengcheng Yu; Zhifeng Gu; Xin Zhan; Yan Wang; Aimin Wang (Marine Biotechnology, 2013)